A Systematic Literature Review on Streetscape Environment: Bibliometric and Visualization Insights - Zhang Weining; Nor Zarifah Maliki; Wang Zebin (Metallurgical and Materials Engineering, 2024)
Streetscape environment (SE), integral to public spaces, has become increasingly significant due to its direct impact on urban life, particularly in the context of rapid urbanization and globalization. The paper aims to investigate the current research situation and progress related to SE research through bibliometrics research on the existing literature. In this study, VOSviewer and Scimago Graphica software were used to visually analyze 257 articles about SE on the Web of Science(WoS) from January 2014 to May 2024. This paper presents the basic characteristics of SE research for the first time, including publication productivity, citation rates, research categories, Web of Science index, and identifies the most cited publications, journals, countries/regions, organizations, and authors. It also maps the network of cooperation among countries/regions, organizations, and authors, identifing their cooperative relationships. Furthermore, the researchers investigate the evolution of SE research hotspots by means of keyword co-occurrence analysis and co-citation reference analysis. The study suggests that while SE research is advancing, there is a critical need for strengthened inter-organizational and author collaboration to facilitate a more profound investigation of SE-human relationship, SE design, and other emerging topics.